Johnny on the Spot-Chronic Inflammation Is Driven by HMGB1 - Gorgulho, Carolina M.; Romagnoli, Graziela G.; Bharthi, Rosh; Lotze, Michael T. (Frontiers in Immunology, 2019)
Although much has been made of the role of HMGB1 acting as an acute damage associated molecular pattern (DAMP) molecule, prompting the response to tissue damage or injury, it is also released at sites of chronic inflammation including sites of infection, autoimmunity, and cancer. As such, the biology is distinguished from homeostasis and acute inflammation by the recruitment and persistence of myeloid derived suppressor cells, T regulatory cells, fibrosis and/or exuberant angiogenesis depending on the antecedents and the other individual inflammatory partners that HMGB1 binds and focuses, including IL-1β, CXCL12/SDF1, LPS, DNA, RNA, and sRAGE. Just as acute inflammatory cells including neutrophils, NK cells, mesangioblasts, and inflammatory macrophages characterize HMGB1 driven inflammation, chronic inflammation shaped by HMGB1 involves more myeloid and plasmacytoid dendritic cells driving lymphoid recruitment and the unusual biology of tissue resident memory T-cells, fibrosis, and neoangiogenesis. Exosomes, carrying HMGB1, and other instructive molecules are released and shaped by many cells in the chronic inflammatory environment. Understanding the defining roles of REDOX, DAMPs and PAMPs, and the host response in chronic inflammation requires an alternative means for positing HMGB1’s central role in limiting and focusing inflammation, distinguishing chronic from acute inflammation.